Assessment of a proposed fluidized-bed air separation process - Kolhammar, Cim; Nyholm, Emil (My University, 2011)
This report investigates the eligibility of oxygen carrier materials of oxygen-uncoupled nature (exemplified by the metal complex CuO/Cu2O) for air separation, with focus on the power industry and oxy-fuel combustion. The influence of a number of parameters is assessed and attempts of process integration reported. The cost of producing a given flow of oxygen in terms of fuel, heat and electricity required is reported and compared with that of conventional cryogenic air separation. At a given temperature, the investigated metal complex has an equilibrium relation with the partial pressure of oxygen in the surrounding gas. By varying either temperature or pressure, the metal complex may release or capture oxygen from the surrounding atmosphere. This behavior, on which chemical- looping with oxygen uncoupling (CLOU) is based, is utilized for air separation in the present work. Four different process integration setups of the proposed air separation unit (ASU) are investigated and the resulting energy penalty is compared to the corresponding energy penalty of a cryogenic ASU. Three of the investigated process integrations produce an O2/CO2 mixture suitable as inlet stream in oxy-fuel combustion units while the fourth produces an O2/steam mixture which is later condensed to produce pure O2. One of the process integration setups (with an O2/CO2 mixture as product) includes indirect heat exchanging of the proposed ASU, while the others did not. The remaining two O2/CO2 process integration setups only heat exchanges in- and outgoing streams (not the ASU itself). One of these two O2/CO2 setups operates at ambient pressure while the other has a slight overpressure in one of the two reactors. All O2/CO2 setups achieve higher thermal efficiencies than the reference case with cryogenic ASU. The thermal efficiency of the process integration setup producing O2/steam is much lower than its reference case with cryogenic ASU. The proposed process does not require such heavy cooling or compression as the conventional cryogenic air separation unit dominating the market today. On the other hand, the proposed ASU works at high temperatures and requires extensive heat recovery to maintain good thermal efficiencies when process-integrated. This requires resilient heat exchanger materials, as well as large heat exchange areas as both mediums involved are gaseous. These facts limit the eligibility of the process, as the gains in thermal efficiency might be offset by the increase in maintenance and capital cost for high temperature gas/gas heat exchangers.
Keywords: Energi; Kemisk energiteknik; Energy; Chemical energy engineering